2022
DOI: 10.3389/fonc.2022.859625
|View full text |Cite
|
Sign up to set email alerts
|

Application Value of Radiomic Nomogram in the Differential Diagnosis of Prostate Cancer and Hyperplasia

Abstract: ObjectiveProstate cancer and hyperplasia require different treatment strategies and have completely different outcomes; thus, preoperative identification of prostate cancer and hyperplasia is very important. The purpose of this study was to evaluate the application value of magnetic resonance imaging (MRI)-derived radiomic nomogram based on T2-weighted images (T2WI) in differentiating prostate cancer and hyperplasia.Materials and MethodsOne hundred forty-six patients (66 cases of prostate cancer and 80 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Gui et al. ( 43 ) built a radiomic nomogram combing T2WI-based radiomic features and PSA yielded an AUC of 0.90 in the differential diagnosis of PCa and hyperplasia. Given that various deep-learning- and radiomics-based methods have been proposed for PCa classification, Castillo T et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gui et al. ( 43 ) built a radiomic nomogram combing T2WI-based radiomic features and PSA yielded an AUC of 0.90 in the differential diagnosis of PCa and hyperplasia. Given that various deep-learning- and radiomics-based methods have been proposed for PCa classification, Castillo T et al.…”
Section: Discussionmentioning
confidence: 99%
“…The line was drawn carefully to maintain an approximate distance of 1–2 mm from ALNs margin on CECT images. 326 quantitative radiomics features were extracted for each ROI using AK software 39,40 . These radiomics features were further divided into six categories, including histogram, formfactor, haralick, gray‐level co‐occurrence matrix (GLCM), run length matrix (RLM), and gray level size zone matrix (GLSZM).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated the potential of radiomics models based on T2-weighted MRI in predicting treatment response and prognosis in various types of cancer [ 21 , 22 ]. These models have demonstrated high sensitivity and specificity in differentiating between different tumor types.…”
Section: Introductionmentioning
confidence: 99%